Implementasi Program 5 Bunga Rampai Sebagai Strategi Inovatif untuk Menanamkan Pendidikan Karakter Siswa - Riska Riska; Isti Ayu Oktrianty; Suharyanto H. Soro; Ida Tejawiani (Civiliza Publishing, Indonesia., 2026)
This study aims to describe and analyze the implementation of the Five Flowers Anthology Program as an innovative strategy in instilling character education in students. This study uses a case study approach. Data collection methods include participatory observation, in-depth interviews, and documentation studies. The respondents of this study consisted of the Principal, teachers of grades I-VI, and students. Data analysis uses the interactive model of Miles and Huberman. The results of the study indicate that the implementation of the Five Flowers Anthology Program at SDN 1 Citalang includes five main programs, namely: (1) Seven Poe Atikan Purwakarta Istimewa which is carried out every day with a different character theme (Ajeg Nusantara, Mapag Buana, Maneuh di Sunda, Nyanding Wangi, Nyucikeun Diri, and Betah di Imah); (2) AKPK Program (Religious Affairs and Book Study) through deepening reading and writing of the Qur'an and understanding of the holy book; (3) Anti-Corruption Education Insertion Program through honesty canteen and integrity habits; (4) Child-Friendly School Program (SRA) through the creation of a safe and inclusive learning environment; and (5) Tatanen Program in Bale Atikan through gardening and entrepreneurship activities. The conclusion of this study is that the implementation of the Five Bunga Rampai program as an innovative strategy can instill character education in students. nga Rampai.